Composed material models for nonlinear behavior of reinforced concrete - Dede, Tayfun; Ayvaz, Yusuf (TECHNO-PRESS, 2013)
The purpose of this study is to present different composed material models for reinforced concrete structures (RC). For this aim a nonlinear finite element analysis program is coded in MATLAB. This program contains several yield criteria and stress-strain relationships for compression and tension behavior of concrete. In this study, the well-known criteria, Drucker-Prager, von Mises, Mohr Coulomb, Tresca, and two new criteria, Hsieh-Ting-Chen and Bresler-Pister, are taken into account. It is concluded that the coded program, the new yield criteria, and the models considered can be effectively used in the nonlinear analysis of reinforced concrete beams.
Keywords: composed material model; elastic behavior; plastic behavior; nonlinear analysis; FINITE-ELEMENT-ANALYSIS; RC SHEAR PANELS; WALLS; MEMBERS; Computer Science; Construction & Building Technology; Engineering; Materials Science